"WHAT'S WRONG WITH THE WAY I TALK?" THE EFFECT OF SOUND MOTION PICTURES ON ACTOR CAREERS. (23rd October 2019) - Hanssen, F. Andrew
Abstract : The development of sound motion pictures in the late 1920s provides one of history's most evocative examples of the effect of technological innovation on employment. I begin by exploring the transition to sound, which lasted several years. I then analyze transition's effect on actor employment, and find it to be associated with a substantial increase in career terminations, not only among major stars (which film scholars emphasize), but also among more minor actors. Furthermore, I find that sound raised hazard rates generally. Finally, I calculate that the number of actors employed in movies increased substantially in the sound era.